Drug residues in used syringes in Switzerland: A comparative study. Issue 5 (27th November 2017) - Lefrançois, Elodie; Augsburger, Marc; Esseiva, Pierre
Abstract: Harm reduction services, including needle‐exchange programmes, have been implemented in Switzerland for over 20 years. Their main aim is to lessen the negative social and/or physical consequences associated with illicit drug consumption and, therefore, improve prevention messages. To this end, knowledge of illicit drug consumption practices is necessary. Periodic self‐report surveys are the primary source of data for monitoring drug users' behaviour. Analysis of residual content of used syringes can bring further and objective knowledge about consumed products through analytically confirmed data. Used syringes were sampled in 2 syringe‐exchange facilities in Lausanne. These structures are a bus where the users bring back their syringes (ABS) and an automatic injecting kit dispenser (AIKD). Once syringes were collected, a validated gas chromatography–mass spectrometry (GC–MS) method was implemented in order to detect drugs (licit or illicit) contained in the residual content of used syringes. Cocaine was the most common drug detected alone (39% in ABS and 31% in AIKD), followed by the simultaneous detection of heroin and cocaine (12% and 17%) and heroin and midazolam (12% and 17%). The differences between the illicit drugs distribution of used syringes collected in AIKD and ABS were not statistically significant. Analysis of residual content of used syringes as a monitoring tool is an original approach that has already led to a better understanding of the habits of drug‐injection users. Over the long term, this approach is a powerful tool to track and detect new consumption practices in a quasi‐real‐time. Abstract : Analysis of the content of used syringes provides information about the actual composition of illicit drugs consumed by injecting drugs users. The present study allows data confrontation between 2 sampling campaigns conducted in 2015 and 2016. During this campaign, cocaine was the most common drug detected alone (39% in 2015 and 31% in 2016), followed by the simultaneous detection of heroin and cocaine (12% and 17%) and heroin and midazolam (12% and 17%).